Psychological distress during COVID-19 pandemic in low-income and middle-income countries: a cross-sectional study of older persons in Thailand - Pothisiri, Wiraporn (BMJ Open, 2021)
OBJECTIVE: The COVID-19 situation in Thailand was controlled with various social measures. Much of the information covered in the media and in studies focused on the public health and economic aspects of the pandemic. This study aimed to explore the psychological well-being of older people, which is important especially in an ageing society categorised as low income or middle income due to the limits of economic and healthcare resources. SETTING: The impact of COVID-19 on older persons in Thailand, an online survey, taken across nine provinces within the five regions of the country. PARTICIPANTS: Information was collected from 1230 adults aged at least 60 years old. If an older person was illiterate, unable to access the internet or had a disability preventing them from responding to the survey, an intermediary residing in the community conducted the survey interview. PRIMARY AND SECONDARY OUTCOME MEASURES: The analysis focused on the worries of older adults and the factors associated with psychological distress experienced during the pandemic using logistic regression analysis. RESULTS: The majority of people aged at least 60 years old experienced psychological distress during COVID-19. Employment loss (OR 1.08, 95% CI 0.78 to 1.38), inadequate income (OR 1.77, 95% CI 1.28 to 2.44) and debt incursion (OR 2.74, 95% CI 1.57 to 4.80) were detrimental to psychological well-being. The negative changes in the perception of their health status (OR 1.92, 95% CI 1.23 to 2.99) and decreased life satisfaction (OR 1.49, 95% CI 0.45 to 1.87) also weighed on older Thais. The protective factors for psychological well-being were residing in rural areas (OR 0.46, 95% CI 0.35 to 0.61) and being married (OR 0.75, 95% CI 0.55 to 1.01). CONCLUSION: Observing the concerns of the older population is important for introducing policies that can alleviate their precarious financial and health statuses.